Expansão do ensino superior e identidade docente : desafios de uma profissão em crise - Gonzatto, Cosmo Rafael (2015)
This dissertation deals with the challenges of the teaching profession in the context of expansion of higher education. This expansion caused a number of problems related to the construction of the teaching professional identity, such as casualization and intensification of work, low pay, devaluation of the profession to society, evil appearance be teaching, among others. Faced with these problems, the research set out to address the following questions: How changes in society affected teachers and their professional identity? How the process of expansion of higher education has influenced the construction of the professional identity of a university professor? As the transformations that have taken place within the university contributed to affect the teaching identity? To answer them, these were the established objectives: 1) to investigate the process of expansion of higher education in Brazil, intensified, mainly by developed educational policies during the government of Fernando Henrique Cardoso (1995-2002) and Luiz Inácio Lula da Silva (2003-2010); 2) analyze how this phenomenon of expansion of higher education has affected the teaching professional identity; c) present indicative that can contribute to addressing the problems caused in the teaching professional identity due to the expansion of higher education phenomenon. Due to the particular theme, it was decided to develop the research by analytical-reconstructive method, stopping mainly to bibliographical and documentary research. The methodology consisted of three stages: a) analysis and interpretation of primary data on the expansion of higher education in the period 1995-2010 selected by the INEP database; b) reviewing / Reconstructive the construction of teacher identity arising from changes in society and the university in recent decades, the process of casualization and intensification of teaching, the characterization of malaise teaching and the emergence of a new teacher professional profile, through the framework provided by Carvalho (2015), Catani (2006), Cicillini and Cunha (2014), Claro and Prophet (2015), Cunha (2013), Costa (2000), Diniz-Pereira (2011), Hall (2006 ), Mancebo, Maués and Chaves (2006), Massetto (2003), Miranda and Melo (2012), Morgado (2011), Morosini (2000), Novoa (1995), Penin (2009), Picado (2015), Veiga ( 2014) and Zabalza (2004); c) systematization of a set of proposals to help overcome the problems faced by teachers in building their professional identity against the background of expansion of higher education. Among the produced results, and the systematization of the scenario that characterized the expansion of higher education in Brazil occurred in the last two decades and as such expansion has affected the construction of teacher identity, the survey indicated the development of teacher education policies promoted by the institutions themselves as an effective action to address the problem of teacher identity.